Does lengthening the school day reduce the likelihood of early school dropout and grade repetition : Evidence from Colombia (2013)
Previous research on the effects of the length of instructional time has found that academic performance is higher when more time is spent in instruction. These findings have been reported in research examining both the length of the school day, as well as the length of the school year (Patall, Cooper, & Allan, 2010). However, most research on the topic has focused on academic assessments, such as standardized tests, or on longer-term outcomes, such as wages. Overlooked in these studies are the more proximate measures of schooling that also influence student trajectories. Specifically, as yet, no analysis has focused on the effects of the length of school schedule on the likelihood of grade repetition, nor on the risk of dropping out of school before graduation. In this analysis, we use data from a new source in Colombia to examine the effects of a change from half-day schooling (media jornada) to full-day schooling (jornada completa) on near-term student outcomes